Paradigms, Models, and Counterfactuals: Decolonializing the Study of Islam in Indonesia - Woodward, Mark (Studia Islamika, 2025)
Decolonializing the study of Islam in Indonesia is a complex process. It involves not only the critique of colonial paradigms as instruments of domination and assessment of the ways in which they have shaped “normal science” (Kuhn 1962) research, but also the ways in which findings from them can contribute to the development of post-colonial, post-orientalist perspectives. This paper focuses on three themes. First: the ways in which research by two important colonial scholars concerned with Indonesian Islam, Stamford Raffles (1781-1826) and Christiaan Snouck Hurgronje (1857-1936) contributed to the formation of paradigms that endured for more than a century; second: the ways in which these paradigms contributed to the development of models of Indonesian Islams and finally steps necessary for the development of genuinely post-colonial, post-orientalist models and paradigms. Exploration of these issues relies on analytic tools from cultural anthropology, the philosophy of science and political science.